Locating colonization at the Jacobean Inns of Court - Working, L (Cambridge University Press, 2017)
Beyond charters, printed propaganda, and cosmographies, aspiring statesmen in Jacobean England engaged with Native Americans in commonplace books, poetry, court masques, and political debate. Rather than representing a remote ‘other’, this article contends that barristers and students of the law were fascinated by the perceived savagery of indigenous peoples because it allowed them to explore, interrogate, and define their own civility. The result was a cross-over between developing English articulations of their own behaviour and political responsibilities, and a rising enthusiasm for colonizing America. With their Whitehall masques and passionate pleas in parliament on behalf of Virginia and Virginian tobacco, members of the Inns engaged in a subversive wit culture that reconciled the exotic with the language of duty and good conduct, and helped turn colonization into a recognizable – and, for the first time, fashionable – element of early seventeenth-century political culture. By considering written discourse alongside tobacco smoking and court masques, this article contends that a broad approach to the socio-cultural world of Jacobean politics reveals some ways through which gentlemen consciously projected their civil state as one that might be strengthened, rather than weakened, by turning to America as a viable theatre for political involvement.